Persepsi Loyalitas Konsumen Terhadap Produk (Survey konsumen J.CO Donuts & Coffe) - S Suhairi (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2020)
This research is a perception of consumer loyalty regarding the latest food and beverage choices of cake donuts towards trend setter product brands J.CO Donuts & Coffe. The purpose of this study is to know the direct reaction of the lovers of donuts (brand loyalty) products indirectly already attached to the heart (One Heart) without turning in another heart. The qualitative research method is based on observations and respoden surveys selected by regular customers and customers who consume food and beverage cake donuts brand J.CO Donuts & Coffe. For the data collection, researchers engaged about 100 respondents selected by consumers of two defense locations namely manhattan plaza medan, Podomoro city deli medan. The results of the data interviewed showed 80% brand loyalty is mainly the quality of products, packaging, service and groceries processed guaranteed halal, in addition there is also a respondent's answer 20% that location and comfort is the periority of consumer satisfaction.